The Selective Closure of Civic Space. (31st July 2021) - Roggeband, Conny; Krizsán, Andrea
Abstract: Scholars and NGOs have been raising alarms about the increasing political restraints that civil society organizations face globally. In this paper, we argue that closure is in fact a selective mechanism: governments attempt to reorganize civic space through a dual process of selective in‐ and exclusion of civil society organizations. Civil society organizations identified as critical of or even anti‐government face obstruction and restraints, whereas simultaneously the space and state support for organizations identified as pro‐government is expanded. Governments instrumentalize certain civil society organizations to their own benefit: they are sponsored and used to influence the realm of civil society in ways that directly legitimize state power and maintain an appearance of democracy. We illustrate our claims by discussing the reorganization of civic space in some countries of Central and Eastern Europe through the case of women's rights activism. Abstract : The developments in Croatia, Hungary and Poland illustrate that rather than closure we see a reconfiguration of civic space. We find that the space of women's rights organizations is curbed, while simultaneously anti‐gender equality organizations have increased access to the political arena and funding channels.